Peran Inovasi Teknologi pada Good Corporate Governance dan Kinerja Keuangan : Studi Empiris pada Perusahaan Sub Sektor Food and Beverage di Indonesia - Annisa Safitri; Irdha Yusra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study was conducted to determine the effect of managerial ownership and institutional ownership on financial performance in food and beverage sub-sector companies with technological innovation as a mediating variable. The population in this study includes food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2019-2023 with a sample size of 100 companies selected based on the purposive sampling method. Data analysis in this study was carried out using a multiple linear regression model and estimated using the SmartPLS 4 program. Classical assumption tests and inner models were also carried out before the hypothesis was tested. Based on the results of the data analysis in the study, it shows that managerial ownership and institutional ownership do not affect financial performance. Managerial ownership and institutional ownership have a negative and significant effect on technological innovation. Technological innovation has a negative and significant effect on financial performance. Technological innovation significantly mediates the effect of the relationship between managerial ownership and institutional ownership on financial performance.